Berbagai Kemungkinan Potensial dalam Penerjemahan Personal Pronoun - Saehu, Andang (Jurnal Penerjemahan, 2020)
This article reviews and discusses the potential possibilities of personal pronouns translation of which they could be found in some novels and movie subtitles. The readers or movie-goers are frequently geting confused or being curious: “how can the pronoun she be translated into Moana? How can the pronoun I be transferred into kita?” Having analyzed, there are some techniques of translation that are potential to translate the personal pronouns variously, they are amplification, reduction, discursive creation, dan particularization. Keywords: Personal Pronoun, Translation Technique, Saving Fish from Drowning, Discursive Creation, Particularization.